Effect of TikToK application on interpersonal communication among university students in Somalia: A Case study at Red Sea University - Malenge, Ezekiel Ingudia; Mohamed, Abdirahman Mukhtar; Abdinor, Abdullahi Bashir (UIN Raden Mas Said Surakarta, 2024)
TikTok application allows individuals to creatively express themselves through brief videos showcasing activities such as dancing, singing and other daily activities. Its popularity is on the rise, particularly among the youth. Nevertheless, it's also facing significant scrutiny. This study aims to gather and analyze social media usage data, specifically focusing on TikTok. It seeks to understand how individuals engage with the app and to evaluate whether its usage negatively impacts interpersonal communication among young people. Participants between the ages of 18 - 32 participated in the survey. The sample used in this study had 316 participants using purposive and quota-sampling techniques. The technological acceptance model is used in this study. SPSS data analysis app was used to analyze the data. The results revealed that the more time students spent on TikTok, the more they became unfocused when trying to interact with their peers. Similar results were noticed when considering losing touch with friends. Their attention was likely to be diverted during discussions. The more they used TikTok, the less attention tended to reduce. The findings indicated that Tik Tok might affect university student's abilities to interact personally. Therefore, interpersonal communication is gradually losing its significance as a catalyst of creativity. The interpretation of the data will aid in the development of techniques to reduce the harmful effects reinforce interpersonal communication and reduce students' addiction to TikTok.